Menstrual experience of adolescents in the USA: protocol for a scoping review - Deborah J Shim; Ronke Olowojesiku; Bryanna Moppins; Daye Park; Jasmine O Patterson; Samantha A Schoenl; Julie K Gaines; Edwin V Sperr; Amy Baldwin (BMJ Open)
Introduction In recent years, there has been a growing desire to address issues related to menstruation, particularly for adolescent girls. In low-income and middle-income countries, prior literature review of the adolescent menstrual experience suggests the need for further research into the impact and efficacy of interventions with this population. There is evidence to suggest the need for initiatives and research in higher-income countries like the USA. To date, the body of research on adolescent menstrual experience in the USA remains uncharacterised. Therefore, we propose a scoping review of the literature on this subject to better inform on areas for future primary study.Methods and analyses Using the framework proposed by Arksey and O’Malley and expounded on by Levac et al and the Joanna Briggs Institute, we will search electronic databases (MEDLINE, CINAHL, PsycINFO, Web of Science, ProQuest Public Health Database, Social Science Citation Index, Social Services Abstracts and SocINDEX) and grey literature for relevant studies in consultation with experienced librarians. The abstracts and full-text from each reference will be screened by two independent reviewers for inclusion. Bibliographic data, study characteristics and themes will be extracted from studies selected for inclusion using a rubric created by the research team. Findings will be summarised and a list of subject areas for future primary research will be generated in consultation with stakeholders. The review will be conducted using the Preferred Reporting Items from Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines.Ethics and dissemination Formal ethics training for this study is not required, as the research team will review publicly available studies. Stakeholders working in adolescent and menstrual health were consulted in designing this review. We will share key findings with stakeholders and in scholarly journals at the conclusion of the review.